2019
DOI: 10.4103/eus.eus_89_17
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of subepithelial lesions of the stomach and esophagus by contrast-enhanced EUS: A retrospective study

Abstract: Background and Objectives: Subepithelial lesions (SELs) of the upper part of the digestive tract are rare, and it can be difficult to characterize them. Recently, contrast-enhanced endosonography (EUS) and elastometry have been reported as useful adjuncts to EUS and EUS-guided fine needle aspiration (EUS-FNA) in cases of pancreatic mass and lymph node involvement. The aim of this retrospective analysis was to evaluate whether contrast-enhanced EUS can discriminate benign submucosal lesions from ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 33 publications
(39 reference statements)
1
25
0
2
Order By: Relevance
“…Gastric SMTs can be exactly diagnosed by EUS [6,7]. Considering the malignant potential of some SMTs, especially when the tumor size is more than 20 mm, resection is recommened for the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric SMTs can be exactly diagnosed by EUS [6,7]. Considering the malignant potential of some SMTs, especially when the tumor size is more than 20 mm, resection is recommened for the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…O schwannoma possui positividade, dentre os marcadores imunohistoquímicos, para proteína S-100 e GFAP e negatividade para CD117 e SMA (HUNG et al, 2008;CHEN et al, 2006). O papel da quimioterapia e radioterapia, como tratamento adjuvante, por sua vez, permanece indefinido, sendo o tratamento de escolha restrito a ressecção cirúrgica oncológica (HUNG et al, 2008;MORO et al, 2017;TRINDADE et al, 2018). Não há consenso, quanto ao seguimento clínico, sendo que alguns serviços de renome optam por reavaliação semestral (IWATA et al, 2018).…”
Section: Discussionunclassified
“…It is difficult to distinguish GIST from benign submucosal lesions on fundamental B-mode EUS images. There have been some reports that CH-EUS is useful in distinguishing GIST from benign SET, [8][9][10][11][12] as GISTs had hyper-enhancement Fig. 1.…”
Section: Diagnosis Of Gists With Ch-eusmentioning
confidence: 99%
“…5,6 However, it is reportedly difficult to differentiate small GISTs from leiomyomas because of a difference in the shape, echogenicity, and homogeneity of EUS. 7 It was reported that contrast-enhanced harmonic (CH) imaging of EUS was useful in distinguishing GIST from benign SET; [8][9][10][11][12] 10% to 30% of GISTs have a malignant clinical course. Therefore, it is necessary to estimate the malignancy potential of GIST by examining the pattern of microvasculature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation